SYNTHESIS AND CHARACTERIZATION OF NEW BINARY AND TERNARY PALLADIUM AND PLATINUM COMPLEXES AFFECTIVE TO ANTITUMOR - Al-Radadi, Najlaa S.; Ramadan, Ramadan M. (European Scientific Journal, ESJ, 2014)
Binary and ternary complexes derived from ligands containing Oxygen, suppler and Nitrogen as donor atoms with Pd2+ and Pt2+ ions were synthesized. The isolated solid complexes were characterized by elemental analyses and spectral (IR, 1H-NMR, mass spectrometry) measurements. The biological efficiency of the synthesized complexes on antitumor, antibacterial and antifungal was investigated. The results reveal that these complexes have strong affinity against the growth of bacteria and fungi. The mode of action may involve the formation of hydrogen bonding between the O and N donors and the active centers of the cell constituents, resulting in interference with the normal cell process. The biological results obtained were compared with that obtained using standard tetracycline as antibacterial and amphotericin B as antifungal. The complexes, PtL3L9 and PtL3L10, are considered as strong anticancer drugs, which have enhanced high biological activity.